THE INDONESIAN TEACHERS’ DILEMMAS FROM COLONIAL TO REFORMASI ERA: NON-PERMANENT TEACHERS’ WELFARE AND STATUS ISSUES (Paramita: Historical Studies Journal, 2019)
This article begins with the historiographic condition of teacher and teacher education which are still rare in demand in Indonesia. The purpose of this article is to describe historically the condition of teacher education, teacher welfare, and teacher status in Indonesia since the Dutch East Indies era to the Reformation era. The sources of the data for this paper are mostly from documents concerning on teacher policies in the past. Oral sources are also used as the complement to the research data. The important findings in this research are (i) there were differences in teacher education between the Dutch East Indies era and independence era that in the colonial era, teacher welfare and status were guaranteed by the government, but the education was still exclusive and very difficult to access by Bumiputera; (ii) teachers in the Japanese colonial era functioned as a means to make Japan win in the Greater East Asia war, welfare was not taken into account; and (iii) during the independence era, the improvement of the teacher status and welfare until reformation era was still becoming a perpetual problem, one of which fulfilled the public discourse was the problem of non-permanent teachers. Historical factors should be considered in managing teacher education and teacher as profession. Therefore, teachers must be seen as historical objects which can enrich Indonesian historiography.Keywords: historiography of teacher, teachers’ welfare, teachers’ dilemma, non-permanent teacher. Artikel ini berangkat dari kondisi historiografi guru dan pendidikan keguruan yang masih jarang diminati di Indonesia. Tujuan penulisan artikel ini adalah mendeskripsikan secara historis kondisi pendidikan keguruan, kesejahteraan, dan status guru di Indonesia sejak masa Hindia Belanda hingga Reformasi. Sumber data tulisan ini lebih banyak berasal dari dokumen-dokumen seputar kebijakan tentang guru di masa lalu. Digunakan pula sumber lisan sebagai pelengkap data penelitian. Temuan penting penelitian ini adalah (1) terdapat perbedaan pendidikan keguruan sejak masa Hindia Belanda hingga kemerdekaan, pada masa kolonial, masalah status dan kesejahteraan guru telah dijamin oleh pemerintah, namun pendidikan masih bersifat eksklusif dan sangat sulit diakses oleh kalangan Bumiputera; (2) guru di masa Jepang berfungsi sebagai alat untuk memenangkan Jepang di dalam perang Asia Timur Raya, masalah kesejahteraan tidak terlalu diperhitungkan; dan (3) pada masa kemerdekaan, perbaikan status dan kesejahteraan guru hingga reformasi masih menjadi masalah yang tidak kunjung selesai, salah satu yang memenuhi dikursus publik adalah masalah guru honorer. Faktor historis harusnya dipertimbangkan dalam mengelola pendidikan keguruan dan profesi guru. Oleh sebab itu, guru harus dipandang sebagai objek sejarah yang dapat memperkaya historiografi Indonesia.Kata kunci: historiograi guru, kesejahteraan guru, permasalahan guru, guru tidak tetap